STUDY OF THE NUTRITIONAL PROPERTIES OF GLUTEN-FREE FLOUR FROM CEREAL AND PSEUDO-CEREAL CULTURES - CHORNA, NINA; POLIATYKINA, YULIIA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Celiac disease is a chronic autoimmune disease characterized by inflammation and damage to the lining of the small intestine due to a negative immune response to gluten, a protein fraction found in wheat, barley, rye, and oats. People with celiac disease cannot properly digest these proteins, which leads to impaired absorption of nutrients and, ultimately, to the development of nutritional imbalances and several related diseases, such as anemia, osteoporosis, and others. One of the main treatment methods is a gluten-free diet, which is the only effective therapy. However, such a diet has certain limitations regarding the nutritional, technological, and sensory quality of the products that make it up. Given the limitations associated with a gluten-free diet, many studies have focused on improving the nutritional properties of gluten-free products, particularly bakery and confectionery products. Important aspects include the use of alternative types of flour rich in nutrients, such as a variety of cereals and pseudo-cereals. They allow not only to enrich the diet of patients with celiac disease, but also provide a wider selection of products, which makes the diet more varied and useful. When designing a gluten-free diet, it is important to consider that different types of flour can have different contents of nutrients, such as proteins, fats, carbohydrates, fiber, trace elements and amino acids. In general, a variety of gluten-free flours from cereals and pseudocereals offer great potential to enrich the diet of people with celiac disease. The use of these alternative flours in the food industry not only helps to improve the nutritional value of gluten-free products but also contributes to the development of economically viable solutions, such as recovering food industry by-products and ensuring food security in developing countries. However, it is important to consider certain disadvantages, particularly the low content of some trace elements, which may require additional enrichment of products or the use of other sources of these substances. Accordingly, future research should focus on improving the processing technologies of gluten-free products to preserve their nutritional value and improve organoleptic properties, which will provide high-quality and useful products for people with celiac disease. Thus, finding new alternative sources of gluten-free flour and improving their production technology is an important aspect of improving the health of people with celiac disease and ensuring variety and balance in their diet.